2019
DOI: 10.1177/1535370219831437
|View full text |Cite
|
Sign up to set email alerts
|

Placental Neuropeptide Y (NPY) and NPY receptors expressions and serum NPY levels in preeclampsia

Abstract: Neuropeptide Y (NPY) has been reported as a vasoconstrictive substance that might be associated with preeclampsia. NPY mediates different effects via its specific NPY receptors. NPY action via Y1 receptor (Y1R) and/or Y5 receptor (Y5R) induces vascular smooth muscle cells proliferation while it is implicated in angiogenesis via Y2 receptor (Y2R) and/or Y5R. The objectives of this study were to (1) compare placental NPY, Y1 receptor (Y1R), Y2 receptor (Y2R), and Y5 receptor (Y5R) expressions between normal (NP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Systemic levels of neuropeptide Y (NPY), a peptide that acts as a sympathetic activator and vasoconstrictor, were found to be elevated in preeclampsia patients as compared to the normal pregnancy population [ 23 , 24 ]. The authors posit that decreases in the expression of NPY receptors probably leads to decreased angiogenesis and vasodilation [ 25 ]. It is plausible that NPY may function through upregulated levels of the neuropeptide Y-4 receptor ( NPY4R ) to induce vasoconstriction, although future studies need to look into the actual expression of this receptor among preeclamptic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic levels of neuropeptide Y (NPY), a peptide that acts as a sympathetic activator and vasoconstrictor, were found to be elevated in preeclampsia patients as compared to the normal pregnancy population [ 23 , 24 ]. The authors posit that decreases in the expression of NPY receptors probably leads to decreased angiogenesis and vasodilation [ 25 ]. It is plausible that NPY may function through upregulated levels of the neuropeptide Y-4 receptor ( NPY4R ) to induce vasoconstriction, although future studies need to look into the actual expression of this receptor among preeclamptic patients.…”
Section: Discussionmentioning
confidence: 99%
“…19 Previous studies have shown that changes in NPY could cause some diseases with vascular lesions, promote angiogenesis, and cause HP. 20…”
Section: Discussionmentioning
confidence: 99%
“…19 Previous studies have shown that changes in NPY could cause some diseases with vascular lesions, promote angiogenesis, and cause HP. 20 Engstr€ om et al 21 reported a pivotal role for NPY-dependent signaling in mediating the rapid feed-inducing effect and the acute glucose regulatory function that is governed by AgRP neurons. In our study, plasma NPY was visibly higher in T2DM with HP compared with T2DM patients without HP and normal individuals.…”
Section: Discussionmentioning
confidence: 99%
“…At least three receptors have been identified on ECs, namely, Y1R, Y2R, and Y5R ( Figure 1 ). NPY at the physiological concentrations of eNOS and VEGF, stimulated endothelial cell proliferation, germination, migration, and adhesion, and induced ischemic angiogenesis and intimal thickening ( 43 , 45 ), by binding to Y1R, Y2R, and Y5R ( 25 , 46 , 47 ). In AS, abnormal neovascularization in plaques not only accelerates plaque progression but also increases the risk of plaque rupture and hemorrhage ( 48 ).…”
Section: Npy and Endothelial Functionmentioning
confidence: 99%